2019
DOI: 10.3390/agronomy9120777
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Iron and the Influence of Vitamin a in Biofortified Foods

Abstract: Inadequate eating habits, among other factors, lead to nutritional deficiencies worldwide. Attempts have been made to control micronutrient deficits, such as biofortification of usually consumed crops, but the interaction between food components may affect the bioavailability of the nutrients. Thus, this study aimed to evaluate the effect of pro-vitamin A on the bioavailability of iron in biofortified cowpea and cassava mixture, compared to their conventional counterparts. The chemical composition of the raw m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Microgreens, like vegetables, can be biofortified with various elements (e.g., iron, selenium, silicon, or iodine) by increasing their concentration in the medium or spraying them with compounds, thus providing missing minerals in the human diet [ 12 ]. Previous studies show good absorption of that element from biofortified plants, which may be due to the high content of ascorbic acid in the plants, among other things [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microgreens, like vegetables, can be biofortified with various elements (e.g., iron, selenium, silicon, or iodine) by increasing their concentration in the medium or spraying them with compounds, thus providing missing minerals in the human diet [ 12 ]. Previous studies show good absorption of that element from biofortified plants, which may be due to the high content of ascorbic acid in the plants, among other things [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…No differences in hemoglobin levels, but hemoglobin levels similar to the ferrous-sulfate-supplemented group [121] Red mottled beans (Phaseolus vulgaris L.)…”
Section: Bioavailability Of Minerals From Biofortified Raw Materialsmentioning
confidence: 93%
“…To date, research work has used laboratory animals (rats, usually Wistar) but also other species (Table 3). Depending on the element to be analyzed, the hemoglobin depletion-repletion method (Fe), analysis of micronutrient contents in serum, urine, and feces, and stable isotopes have been used [121]. It is also possible to perform micronutrient content analysis in tissues [137,138], which can allow for indirect determination of the biofortification efficacy in the context of animal viability.…”
Section: Humansmentioning
confidence: 99%
“…Hemoglobin regeneration efficiency (HRE), a method of assessing in vivo iron bioavailability of food products, is determined as the percent conversion of dietary iron into hemoglobin-iron in blood. 42 Antunes et al 43 found that biofortified cowpea exhibited excellent in vivo iron bioavailability with high HRE values in rat models, suggesting a greater iron absorption efficiency from biofortified cowpea in the intestinal tract. Additionally, a greater hemoglobin regeneration efficiency was found in iron-deficiency rats fed with tripeptide iron, and anemia symptoms of rats resumed to normal or improved after administration with tripeptide iron.…”
Section: Dietary Iron Absorption and Regulationmentioning
confidence: 99%